STUDY SEARCH FOR ALUMNI HEALTH POLITEKNIK MINISTRY OF HEALTH KUPANG GRADUATE 2009 - 2012 - BEATRIX SOI; YULIANA DAFROYATI; DOMINGGOS GONSALVES; NI NYOMAN YULIANI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2016)
Health Polytechnic Ministry of Health of Kupang has released its graduates as many as 6521 people for about 10 years since the first batch of 2002 up to force to 10 graduates in 2012. Of this number is mostly Diploma III Regular Class, some Diploma III Special Path and Special Program and Diploma IV Midwife Educator as well as Diploma IV Medical surgery. Since the establishment of Poltekkes Kemenkes Kupang until now has never been done research on the level of satisfaction of stakeholders of Pole Kemenkes Kupang graduates. In order to improve the quality of its graduates, it is necessary to conduct a study of Poltekkes alumni of Kemenkes Kupang to obtain data on absorption, length of time before getting a job, and job suitability with their area of expertise. From this research, it is expected that the Health Education Polytechnic Institute Manager of the Ministry of Health of Kupang gets a lot of information about the things that need to be improved in curriculum development and for the implementation of education in the future. Types of Quantitative Observational Research are collected and analyzed descriptively in the form of tables and graphs. This research is useful for Institutions to get feedback from Graduates and can be used as real data to design curriculum and development of educational institutions.